Investigation of Scattered Power and Cross-Polarization Effects on Linearly Polarized Waves under Sandstorm Conditions - Fowzi S. Alarabi (Libyan Journal of Medical and Applied Sciences, 2025)
Sand and dust storms (SDST) can significantly affect the propagation of microwave and millimeter-wave signals. These atmospheric conditions reduce visibility due to the high concentration of suspended particles, which enhances the scattering of electromagnetic waves. The extent of signal power loss and distortion depends on particle characteristics, such as size, shape, and orientation, as well as wave polarization and incidence angle. In this work, the modified Rayleigh approximation is employed to estimate the scattered power and the cross-polarization generated by sand and dust particles. This formulation enables accurate characterization of the scattering behavior of non-spherical particles with triaxial ellipsoidal geometry in the microwave and millimeter-wave frequency ranges. The results reveal a clear dependence of the scattered power distribution between horizontal and vertical polarization components on particle geometry, with the effect being more pronounced in the case of horizontally aligned particles, a configuration considered physically realistic due to gravitational settling and the influence of horizontal wind shear. Scattered power in the microwave and millimeter-wave bands is further formulated as a function of meteorological visibility by establishing a relationship between sand/dust particle concentration and visibility range. The results demonstrate that scattering effects intensify considerably with the severity of SDST, as indicated by reduced visibility. In this study, cross-polarization discrimination (XPD) is evaluated as the ratio between the received co-polarized power and the corresponding power in the orthogonal component, in order to quantify the transfer of energy into the cross-polarized state induced by dust particles. Such studies are essential for the design of terrestrial wireless communication systems in desert environments, particularly polarization-sensitive links operating at high frequencies (40–80) GHz).